HUBUNGAN ANTARA TINGKAT PENDIDIKAN TERHADAP PENGETAHUAN MASYARAKAT TENTANG HIPERTENSI DI POSBINDU DESA SRIGADING, SANDEN, BANTUL, YOGYAKARTA - Fitria Dhirisma; Idhen Aura Moerdhanti (Akademi Farmasi Indonesia Yogyakarta, 2022)
The results of basic health research or Riskesdas in 2018, an increase in the prevalence of non-communicable diseases such as cancer, stroke, kidney disease, diabetes mellitus and hypertension, with the prevalence of hypertension in DIY 32.86%. Providing correct information is expected to be able to increase public knowledge about hypertension. One of the factors that can affect knowledge is a person's education level. The higher the level of education, the higher the knowledge. This study aims to determine the relationship between education level and public knowledge about hypertension in Posbindu, Srigading, Sanden, Bantul. This study used an observational method. Collecting data using a closed questionnaire which is given directly to the respondents. The data obtained were analyzed using the chi-square, with a 95% confidence level in the form of a table of the relationship between education level and public knowledge about hypertension with a sample size of 70 respondents. The results showed that there was no significant relationship between education level and public knowledge about hypertension with a significance value of 0.593. The majority of respondents have good knowledge of 82.9%, this is supported by an active environment in the implementation of Posbindu activities which are carried out regularly.